Peran Kepuasan Kerja Dalam Memediasi Pengaruh Perubahan Organisasi Dan Kerjasama Tim Terhadap Kinerja Pegawai Balai Pelatihan Vokasi Dan Produktivitas Kendari - Usman Usman; Amran Amran; La Hatani; Muh. Masri (ProBisnis : Jurnal Manajemen, 2026)
The purpose of this study is to test and analyze the influence of: 1) organizational change on job satisfaction. 2) teamwork on job satisfaction. 3) organizational change on employee performance. 4) teamwork on employee performance. 5) job satisfaction on employee performance. 6) organizational change affects employee performance through job satisfaction. 7) teamwork affects employee performance through job satisfaction. The research method used quantitative research. The data used were secondary and primary data. Data analysis used Smart PLS 4.0 software. The sampling technique used a saturated sample of 52 employees at the Kendari Vocational Training and Productivity Center Office. The results of the study indicate that; 1) Organizational change has a positive and significant effect on job satisfaction. 2) Teamwork has a positive and significant effect on job satisfaction. 3) Organizational change has a positive and significant effect on employee performance. 4) Teamwork has a positive and significant effect on employee performance. 5) Job satisfaction has a positive and significant effect on employee performance. 6) Organizational change has a positive and significant effect on employee performance mediated by job satisfaction. 7) Teamwork has a positive and significant effect on job satisfaction mediated by job satisfaction.